Manufacturing DNA microarrays of high spot homogeneity and reduced background signal - Diehl, Frank (Oxford University Press, 2001)
Analyses on DNA microarrays depend considerably on spot quality and a low background signal of the glass support. By using betaine as an additive to a spotting solution made of saline sodium citrate, both the binding efficiency of spotted PCR products and the homogeneity of the DNA spots is improved significantly on aminated surfaces such as glass slides coated with the widely used poly-l-lysine or aminosilane. In addition, non-specific background signal is markedly diminished. Concomitantly, during the arraying procedure, the betaine reduces evaporation from the microtitre dish wells, which hold the PCR products. Subsequent blocking of the chip surface with succinic anhydride was improved considerably in the presence of the non-polar, non-aqueous solvent 1,2-dichloroethane and the acylating catalyst N-methylimidazole. This procedure prevents the overall background signal that occurs with the frequently applied aqueous solvent 1-methyl-2-pyrrolidone in borate buffer because of DNA that re-dissolves from spots during the blocking process, only to bind again across the entire glass surface.